The Role of Natural Killer Group 2, Member D in Chronic Inflammation and Autoimmunity - Marina Babic; Marina Babic; Chiara Romagnani; Chiara Romagnani (Frontiers in Immunology, 2018)
Current medicine and medical science puts great effort into elucidating the basis of chronicity and finding appropriate treatments for inflammatory diseases; however, the mechanisms driving aberrant immune responses are mostly unknown and deserve further study. Of particular interest is the identification of checkpoints that regulate the function and differentiation of pro-inflammatory cells during pathogenesis, along with means of their modulation for therapeutic purposes. Natural killer group 2, member D (NKG2D) is a potent activator of the immune system, known as a sensor for “induced-self” ligands, i.e., cellular danger signals that, in the context of chronic inflammation and autoimmunity, can be presented by cells being exposed to an inflammatory cytokine milieu, endoplasmic reticulum stress, or cell death. Engagement by such ligands can be translated by NKG2D into activation or co-stimulation of NK cells and different subsets of T cells, respectively, thus contributing to the regulation of the inflammatory response. In this review, we discuss the current knowledge on the contribution of the NKG2D–NKG2DL signaling axis during intestinal inflammation, type 1 diabetes, multiple sclerosis, and rheumatoid arthritis, where the role of NKG2D has been associated either by aberrant expression of the receptor and its ligands and/or by functional data in corresponding mouse models.